THU0446 Usefulness of colour doppler ultrasonography in follow up of giant cell arteritis. (12th June 2018) - Mukoyama, H.; Nishimura, K.; Kadoba, K.; Saito, R.; Waki, D.; Yokota, T.
Abstract : Background: Colour doppler ultrasonography (CDU) in temporal arteries (TA) is useful for diagnosis and follow-up of giant cell arteritis (GCA). 1 However, the usefulness of CDU in carotid arteries (CA) for follow-up of GCA is not fully understood. 2 Objectives: We investigated retrospectively relationship between clinical features and vessel wall thickness of TA and CA on CDU at baseline and during follow-up. Methods: We recruited patients with newly diagnosed GCA in our hospital from January in 2004 to July in 2017. Among 35 patients, both of TA and CA were evaluated by CDU before and after treatment in 14 patients (four male and 10 female). Trained ultrasonographers and rheumatologists evaluated the CDU findings. Vessel wall thickness was evaluated at thickest portion of parietal or frontal ramus of TA, where biopsy was often performed. Intima-media thickness (IMT) of CA was also evaluated at thickest portion in each carotid artery. Results: Average age was 73.2±11.3 years old. Follow-up periods after starting treatment were 244±149 weeks. All patients were diagnosed as GCA according to ACR criteria (1990) or temporal artery biopsy. Twelve patients were complicated with polymyalgia rheumatica (PMR) meeting EULAR/.ACR classification criteria (2012). All patients were treated with oral glucocorticoids (0.2 to 1.0 mg/kg prednisolone, 0.886 mg/kg on average). Immunosuppressants were added in four patients (methotrexate; n=3, tacrolimus; n=1). Aspirin was prescribed in nine patients. Eleven patients (78.6%) had circumferential hypoechoic vessel wall thickness (halo sign) of TA at baseline, and halo signs dissapeared in eight patients during follow-up. Average of vessel wall thickness significantly decreased from 0.665 mm to 0.311 mm (p=0.0016). The vessel wall thickness apparently increased in two patients out of three on clinical relapse, but it didn't increase in those who kept remission. Graphical changes consistent with vasculitis in CA were observed in six patients, who showed hypoechoic thick intima and media on ultrasound or integration of FDG on PET/CT. Average of IMT in CA decreased from 1.167 mm to 0.883 mm (p=0.090) during follow-up in patients with vasculitis on CA. IMT changed little in patients without vasculitis on CA. Improvement rate was significantly higher in CA-involved patients than in CA-non-involved patients (p=0.043). IMT increased during follow-up in two CA-non-involved patients. Difference in B/A between CA involved and non-involved: p=0.043 (Mann-Whitney U test) Conclusions: CDU of temporal arteries is useful for follow-up of GCA. CDU of carotid arteries has limited usefulness only in CA-involved patients. References: [1] Suelves AM, et al. Clin Ophthalmol. 2010; Nov 25;4:1383–4. [2] Hafner F, et al. Eur J Clin Invest2014; 44(3):249–256. Disclosure of Interest: None declared